Blockchain-based Digital Twins for the Industrial Internet of Things - Rajashekar, J. S.; Greeshma, P. P. (Journal of ISMAC, 2022)
Sensory data is used in industrial processes for making decisions, evaluating performance, and measuring risks. To extract useful insights from the data acquired, as well as a system that can guarantee the transmission of reliable data, are needed. To be reliable, physical data must be model-free using numerous overlapping field-of-view sensor origin. Events that occur during the product lifetime supplied for the motive of process monitoring, recognition, and optimum control when dependable data is put down on the blockchain. Given this, The use of digital twins (DTs) to derive intuitive inferences based on the data by spotting flaws with advising preventative solutions before key events occur. We give complete evaluation results of cutting-edge research for blockchain-based DTs Throughout this study, while stressing its important benefits of employing DTs built on blockchain. We propose trustworthy DTs built on blockchain architecture according to recent studies. In DTs built on blockchain, awe emphasise its importance relating to artificial intelligence (AI). We also go about existing and future blockchain-based DT research and implementation difficulties that need to be looked into further.